2008
DOI: 10.1590/s0004-27302008000800028
|View full text |Cite
|
Sign up to set email alerts
|

Prevalence of the polymorphism MTHFR A1298C and not MTHFR C677T is related to chromosomal aneuploidy in Brazilian Turner Syndrome patients

Abstract: Background: Dysfunctions in the folate metabolism can result in DNA hypomethylation and abnormal chromosome segregation. Two common polymorphisms of this enzyme (C677T and A1298C) reduce its activity, but when associated with aneuploidy studies the results are confl icting. The objective of the present study is to analyze the MTHFR gene polymorphisms in women with Turner Syndrome and in a control group, correlating the fi ndings to the chromosomal aneuploidy. Methods: The study comprised 140 patients with Turn… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
1
2

Year Published

2009
2009
2018
2018

Publication Types

Select...
6
2

Relationship

0
8

Authors

Journals

citations
Cited by 27 publications
(17 citation statements)
references
References 26 publications
(29 reference statements)
1
13
1
2
Order By: Relevance
“…Herein, we observed that 11.3% of the population presented as being homozygous (TT) for the variant 677C>T, considering a homozygote prevalence of 13.2% and 1.6% among White and Black races, respectively. In a study concerning the polymorphism 1298A>C, 40% heterozygotes (AC) and 6% mutant homozygotes CC were observed in a healthy Brazilian population [21], consistent with the results of the present study (34.2% AC and 6.2% CC). In the United Kingdom, 44.8% heterozygotes AC and 9.3% mutant homozygotes CC were observed in an elderly population ( n = 1041) [22].…”
Section: Discussionsupporting
confidence: 92%
“…Herein, we observed that 11.3% of the population presented as being homozygous (TT) for the variant 677C>T, considering a homozygote prevalence of 13.2% and 1.6% among White and Black races, respectively. In a study concerning the polymorphism 1298A>C, 40% heterozygotes (AC) and 6% mutant homozygotes CC were observed in a healthy Brazilian population [21], consistent with the results of the present study (34.2% AC and 6.2% CC). In the United Kingdom, 44.8% heterozygotes AC and 9.3% mutant homozygotes CC were observed in an elderly population ( n = 1041) [22].…”
Section: Discussionsupporting
confidence: 92%
“…The MTHFR 677 C→T polymorphism is associated with diminished levels of 5-methylcytosine and DNA hypomethylation (Chen et al, 2010;Friso et al, 2002;Paz et al, 2002), micronucleus formation (Andreassi et al, 2003;Botto et al, 2003), and microsatellite instability (Naghibalhossaini et al, 2010) in the presence of the variant T allele. The homozygous variant genotype of another polymorphism of the MTHFR gene, 1298 A→C, was more frequent in patients with Turner syndrome (de Oliveira et al, 2008), and a higher frequency of the C allele was observed in spontaneous abortions with fetal chromosomal aneuploidy as compared to those with normal fetal karyotypes (Kim et al, 2011), suggesting its involvement in the origin of chromosomal imbalances. The MTR 2756 A→G polymorphism was associated with reduced number of hypermethylated CpG islands of suppressor tumor genes and with higher micronucleus rates in the presence of the MTRR 66 GG variant genotype (Botto et al, 2003;Paz et al, 2002;Zijno et al, 2003).…”
Section: Folate Metabolism Genomic Stability and Genetic Polymorphismsmentioning
confidence: 98%
“…TS is characterized by the absence or abnormality of one sex chromosome in either all or some cells. To date, two studies have evaluated the influence of two common MTHFR polymorphisms (677C>T and 1298A>C) and nondisjunction in Turner syndrome, and have reported conflicting results [Santos et al, 2006;Oliveira et al, 2008]. Therefore, virtually every live-born TS individual must comprise more than one cell line, thus constituting a mosaic [Oliveira et al, 2009;Hook and Warburton, 2014].…”
Section: Introductionmentioning
confidence: 99%
“…Therefore, virtually every live-born TS individual must comprise more than one cell line, thus constituting a mosaic [Oliveira et al, 2009;Hook and Warburton, 2014]. To date, two studies have evaluated the influence of two common MTHFR polymorphisms (677C>T and 1298A>C) and nondisjunction in Turner syndrome, and have reported conflicting results [Santos et al, 2006;Oliveira et al, 2008].…”
Section: Introductionmentioning
confidence: 99%